ID 515 – Mood dysregulation, sex and sex hormones predict stress response circuitry deficits. Issue 3 (March 2016) - Mareckova, K.; Holsen, L.; Admon, R.; Whitfield-Gabrieli, S.; Goldstein, J.M.
Abstract : Inspired by the NIMH RDoC initiative to determine biosignatures associated with regulation of arousal and negative affect across psychiatric disorders, we used a mild visual stress task to conduct a functional magnetic resonance imaging (fMRI) study investigating the impact of depressed mood on stress circuitry function in major depressive disorder, psychosis and healthy controls ( n = 99). fMRI data were analyzed using SPM8 and task-related connectivity was assessed by generalized psychophysiological interaction (gPPI). Hyperactivity in subcortical arousal regions in response to stress was shared across diagnoses. Sex-specific analyses revealed that in females but not males depressed mood predicted increase in R AMYG response and decrease in (1) R AMYG–R HIPP, (2) R AMYG-R OFC, and (3) HYPO–R OFC connectivity during stress. Follow-up analyses showed that the positive relationship between depressed mood and stress-related increase in R AMYG–R HIPP connectivity was present in males with high but not low free androgens. Overall, these findings demonstrated that females with depressed mood were unable to recruit regions inhibiting subcortical arousal during stress, possibly explaining why women are more vulnerable to mood disorders than men, and that testosterone might have protective effects on stress circuitry function in men.